The implementation of cleaner production throughout various industries - Hadi, Genta A. (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: The implementation of cleaner production (CP) has gained significant attention in recent years as a cost-effective strategy to address environmental challenges and improve resource efficiency. Methods: A literature review was conducted to examine the implementation of CP in various industrial sectors and the factors that influence its success. Findings: The review found that the successful implementation of CP is influenced by regulatory and policy frameworks, stakeholder involvement, the availability of technical and financial resources, and the level of awareness and understanding of CP among industrial firms. Conclusion: The adoption of CP practices can lead to significant environmental and economic benefits, including reduced energy and water consumption, reduced waste generation and pollution, and increased competitiveness and profitability. However, challenges to the implementation of CP were also identified, including a lack of awareness and understanding, a lack of financial and technical resources, and a lack of supportive policy frameworks.